Respon Daya Cerna dan Respirasi Benih Ikan Mas (Cyprinus carpio) Pasca Transportasi Dengan Menggunakan Daun Bandotan (Ageratum conyzoides) Sebagai Bahan Antimetabolik [Digestibility Response and Respiration Post Transportation With Bandotan (Ageratum conyzoides) Leaf As Antimetabolic Of Common Carp (Cyprinus carpio) Fry ] - Laksmi Sulmartini; Dewi Nurul Chotimah; Wahju Tjahjaningsih; Thomas V.; Widiyatno Widiyatno; Juni Triastuti (Faculty of Fisheries and Marine Universitas Airlangga, 2009)
Abstract Common carp (Cyprinus carpio) is fish with high metabolism during transportation caused fish stress and could due to impare condition of fry fish and also lead to mortality post transpotation. As effort to minimize high metabolism during transportation was use bandotan leaf as nature antimetabolic so that we need to know how far bandotan effect to condition by digestibility and respiration of common carp fry during post transportation critical periode. The aim of this study was to know condition of common carp fry for 3 days post transportation by digestibility and respiration with bandotan leaf. This study used Complete Random Design. The treatment were A (water 0,5 l) B (bandotan leaf water dose 3,25 g/l) dan C (bandotan leaf water dose 4,5 g/l), each treatment with 6 replications. Primary parameter were digestibility (%) and respiration (time). Secondary parameter were mortality (%), and water quality (disolve oxygen, temperature, ammonia and pH). The result show that bandotan leaf was significantly influenced (p<0,05) to digestibility common carp (Cyprinus carpio) fry at 48 hour post transportion. Bandotan leaf significantly influenced (p<0,05) to respiration common carp (Cyprinus carpio) fry for 72 hour post transportion. Dose of bandotan leaf was 4,5 g/l could used to common carp fry transportation without mortality that was caused by change of digestibility and respiration response.